ДИСТАНЦІЙНЕ НАВЧАННЯ: ДЕЯКІ УМОВИ РЕАЛІЗАЦІЇ (Педагогіка вищої та середньої школи, 2008)
In article are stated some organizing and methodical problems connected with process of the development, introduction and realization of the models of the remote education.